HYBRIDE IMAGING IN ADVANCED MELANOMA: PET/CT in advanced melanoma - Grozdic Milojevic, Isidora (Medical Research, 2023)
Objective: To evaluate the usefulness of 18F-FDG PET/CT in patients with advanced melanoma. Methods: This study included 264 consecutive melanoma patients who were sent for the 18F-FDG PET/CT. The inclusion criteria were: histopathologically verified melanoma stage III or IV; absence of other malignancy / infection; glycemia ≤ 11 mmol/l. The final study population consisted of 220 patients. After the first 18F-FDG PET/CT, the follow-up was performed after 11.81±7.99 months, for therapy response evaluation. Results: Pathological 18F-FDG PET/CT was present in 154 patients. Sensitivity of 18F-FDG PET/CT was estimated as 99%, specificity as 47%. There was no statistically significant difference between 18F-FDG PET/CT findings and gender and MDCT examination (p> 0.05). 18F-FDG PET/CT upstaged 45% patients, especially these with widespread disease. SUV max and inguinal disease localization (in patients who had lower extremities as primary localization of disease) were associated with progression free survival (PFS) (p < 0.05). SUV max (HR 1.03, ,p<0.05) and locally advanced disease (HR 12.02, CI 1.13-148.00, p<0.04) were independent predictors of PFS. Follow up 18F-FDG PET/CT revealed active disease in 18/26 patients. Therapy type (immunotherapy or target therapy) did not correlate significantly with the 18F-FDG PET/CT follow up result (p=0.760, ρ=-0.354). Conclusion: 18F-FDG PET/CT has good sensitivity in evaluation of advanced melanoma. Small lesions and brain localization reduce the specificity of the examination. SUV max and locally advanced disease are predictors of PFS. Follow up 18F-FDG PET/CT should be done at least on 6 months period, only if there is suspicion of presence of active disease.